Effectiveness of Health Promotion Through Animation Video On Knowledge And Attitudes In Stunting Prevention Among Mothers in the Baduy Tribe - Pratiwi, Rita Dwi; Azahra, Jihan Najlah; Kasumawati, Frida; Romlah, Siti Novy; Poddar, Prof. Sandeep (Window of Health : Jurnal Kesehatan, 2025)
Stunting is a growth and development disorder in children due to prolonged malnutrition. Prolonged malnutrition in children can lead to developmental disorders. Indicators of healthy growth include measurements such as weight, height, and head circumference, whereas development is assessed through motor abilities, social and emotional skills, language proficiency, and cognitive functions. Malnutrition can begin during pregnancy and continue in the early stages of a child’s life. Stunting experienced by children can be caused by ineffectiveness in the first 1000 days of life. The aim of the research to determine the influence of Health Promotion through Animation Video on the knowledge and attitude among mothers in efforts to prevent stunting in the Outer Baduy Tribe Area. The study employs a pre-experimental design, utilizing a single group with both pre-test and post-test assessments, with a sample size of 50 participants of purposive sampling as the method for selecting participants. Data was gathered through the use of a structured questionnaire. The p-value obtained was 0.000. Based on the findings, it can be inferred that a significant difference exists in the influence of health awareness promotion with the video animation method on the awareness and attitude of mothers in efforts to prevent stunting in the Baduy Luar Tribe Area. A significant difference exists in the influence of health awareness promotion programs with the animation video technique on the knowledge and attitude of mothers in efforts to prevent stunting in the Outer Baduy Tribe Area.